T Helper Lymphocyte and Mast Cell Immunohistochemical Pattern in Nonceliac Gluten Sensitivity. (7th December 2017) - Losurdo, Giuseppe; Piscitelli, Domenico; Pezzuto, Federica; Fortarezza, Francesco; Covelli, Claudia; Marra, Antonella; Iannone, Andrea; Amoruso, Annacinzia; Principi, Mariabeatrice; Ierardi, Enzo; Di Leo, Alfredo
Abstract : Background and Aims . Nonceliac gluten sensitivity (NCGS) is a gluten-related emerging condition. Since few data about NCGS histopathology is available, we assessed the markers of lymphocyte and innate immunity activation. Materials and Methods . We retrieved duodenal biopsy samples of patients with NCGS diagnosis according to the Salerno criteria. We selected specimens of positive (seropositive celiac disease/Marsh 1-2 stage) and negative (normal microscopic picture) controls. Immunohistochemistry for CD3 (intraepithelial lymphocytes-IELs), CD4 (T helper lymphocytes), CD8 (T cytotoxic lymphocytes), and CD1a/CD117 (Langerhans/mast cells) was performed. ANOVA plus Bonferroni's tests were used for statistical analysis. Results . Twenty NCGS, 16 celiac disease, and 16 negative controls were selected. CD3 in NCGS were higher than negative controls and lower than celiac disease (18.5 ± 6.4, 11.9 ± 2.8, and 40.8 ± 8.1 IELs/100 enterocytes; p < 0.001 ). CD4 were lower in NCGS than controls and celiac disease (31.0 ± 22.1, 72.5 ± 29.5, and 103.7 ± 15.7 cells/mm 2 ; p < 0.001 ). CD8 in NCGS were similar to negative controls, but lower than celiac disease (14.0 ± 7.4 and 34.0 ± 7.1 IELs/100 enterocytes, p < 0.001 ). CD117 were higher in NCGS than celiac disease and negative controls (145.8 ± 49.9, 121.3 ± 13.1, and 113.5 ± 23.4 cells/mm 2 ; p = 0.009 ). Conclusions . The combination of CD4 and CD117, as well as IEL characterization, may be useful to support a clinical diagnosis of NCGS.